Comprehensive assessment of the territory as a part of the environmental and economic feasibility study for the formation of a state nature reserve. Issue 1 (October 2020) - Lyubchenko, E V; Varlamov, A A; Galchenko, S A; Antropov, D V; Hasanov, A Z
Abstract: The article considers the process of creating specially protected natural territories as one of the main and traditional approaches to the conservation of biological diversity in the framework of the implementation of the state environmental policy. Based on an analysis of a number of projects for the creation of specially protected natural territories of federal significance, a recommended list of sections has been compiled for a comprehensive assessment of the territory as a part of the environmental and economic justification for the formation of a state nature reserve.